Weed management in elephant foot yam [Amorphophallus paeoniifolius (Dennst.) Nicholson] - Sekhar, Lekshmi; Thomas, C. George; Sindhu, P.V. (Journal of Tropical Agriculture, 2017)
An experiment was conducted in elephant foot yam to find out alternatives to manual weeding and to formulate an economical weeding schedule. The experiment was laid out in RBD with 10 treatments and 3 replications, and conducted at the College of Horticulture, Thrissur. Chemical and non-chemical methods of weed management were compared. Among the treatments, mulching with black polythene displayed superior growth and yield characters such as height, diameter, volume of corm, and total weight of corm from unit area. Pre emergence application of oxyfluorfen 0.2 kg ha-1 plus manual weeding at 75 DAP and post emergence application of glyphosate 0.8 kg ha-1 plus anual weeding at 75 DAP were the other better treatments. Mulching with black polythene produced higher plant dry weight throughout the crop period irrespective of the crop growth stage. The treatments, mulching with dry grasses and intercropping with cowpea were not effective in suppressing weeds to any marked level as shown by less crop dry weight and yield characters throughout the growth period.